A New Method for Estimating Coarse Root Production in Forest Ecosystem. Issue 2 (7th September 2018) - Van Do, Tran; Sato, Tamotsu; Yamamoto, Mamoru; Kozan, Osamu; Thang, Nguyen Toan; Hai, Vo Dai; Quy, Tran Hoang; Trung, Phung Dinh; Van Thuyet, Dang
Abstract: Below-ground net primary production in forest ecosystems includes root exudates and production of fine roots and coarse roots. A new method to estimate coarse root production is described and applied in an evergreen broadleaf forest, Vietnam. Four 1-m 3 soil blocks were sampled to collect coarse roots, and measured for diameter ( Ø ), length ( L ) and dry mass ( M ) in 2014. Another new five 0.125-m 3 soil blocks were used to measure the coarse root diameter in March 2014 and again in April 2016 to measure the diameter increment. In March 2014, the soil was carefully removed from each 0.125-m 3 block using a shovel and trowel. The exposed coarse roots were carefully marked and measured, and the soil was filled in to cover all the roots so they could continue their natural growth. In April 2016, the soil was removed again, and coarse root diameters were measured at the marked points. Five relationships were established between M and Ø 2 · L for five diameter classes of coarse roots. These five relationships overestimated total biomass by 3.4 percent. Coarse root production at the present study site was 0.99 g m −2 d −1 . It is concluded that in suitable soils, the new method to estimate coarse root production using the allometric relationship between M and Ø 2 · L would be easy and applicable to forest without destructive sampling of standard trees.